Reputation: 79
I have a function but can't success to make it recursive. This is my function without recursion :
function resolution_recursion($tab1, $tab2){
$solution = [];
foreach($tab2 as $nb2){
foreach($tab1 as $nb1){
if(($nb2 + $nb1)%2 != 1){
$solution[] = $nb2 + $nb1;
}
}
}
return $solution;
}
And I would like to make it recursive to make it work like :
$nb_ajout = [2];
$next = [[1,2],[3,4],[5,6],[7,8]];
resolution_recursion(
resolution_recursion(
resolution_recursion(
resolution_recursion($nb_ajout, $next[0]),
$next[1]),
$next[2]),
$next[3]);
I can't find the solution, if you can help me.
Upvotes: 0
Views: 110
Reputation: 79
I think I have found something, not using recursion :
function resolution_recursion($tab1, $tab2){
$solution = [];
$solution[-1] = $tab1;
foreach($tab2 as $key => $tab){
foreach($tab as $nb2){
foreach($solution[$key-1] as $nb1){
if(($nb2 + $nb1)%2 != 1){
$solution[$key][] = $nb2 + $nb1;
}
}
}
}
return $solution;
}
Upvotes: 0
Reputation: 3730
Something like this would do the trick...
function resolution_recursion($tab1, $tab2, $solution = [])
{
if (empty($tab2)) {
return $solution;
}
$set = array_shift($tab2);
foreach($set as $nb2){
foreach($tab1 as $nb1){
if(($nb2 + $nb1)%2 != 1){
$solution[] = $nb2 + $nb1;
}
}
}
if (!empty($tab2)) {
return resolution_recursion($tab1, $tab2, $solution);
}
return $solution;
}
You can find a demo here (the output however means absolutely nothing to me though so hopefully it means something to you lol)
Upvotes: 1